Type A personality as a nonspecific risk factor for cardiovascular disease - Kadłubowska, Monika; Fraś, Małgorzata; Kolonko, Jolanta; Turbiarz, Agnieszka (Nursing Problems / Problemy Pielęgniarstwa, 2013)
Cardiovascular diseases have a multifactorial etiology and their formation is associated mainly with the development of civilization and especially lifestyle characteristic of the developed countries. The basis depending on the psychological factors in the etiology and treatment of heart disease is considered pathophysiological mechanisms. In addition to traditional risk factors also points to the considerable importance of psychosocial factors, which include the Type A personality. There is the involvement of individuals in a permanent struggle to get as large targets in the shortest possible time. This causes the individual to remain in a position of increased tension and fixation of the psychophysical response patterns typical for emergency response. Cope with stress in a non-adaptive, which is an additional, behavioral risk factor for atherosclerosis and development of diseases associated with it, in that cardiovascular disease. Aim of the study was the describe of type A personality in the development of cardiovascular disease. Nursing Topics 2013; 21 (1): 123–127